Empowering nurses: exploring self-managed organizations in Indian healthcare - Malik E.; Shankar S. (My University, 2025)
Background: Given India’s high patient load on the existing healthcare setup, as well as political, social, and organizational challenges, the nursing sector is facing various problems, therefore leading to substandard nursing experiences leading to poor patient care at the parallel healthcare setups, specifically homecare. This paper presents self-managed organizations (SMOs) characterized by a horizontal management structure as an effective alternative to existing hierarchical management structures overladen with bureaucracy. Therefore, we are exploring the strategies at self-managed homecare organizations that can make nursing a better and more productive experience. Method: This study utilized Constructivist Grounded Theory (CGT), employing semi-structured interviews to explore nursing dynamics in horizontal organizational structures. It delved into crucial aspects like finances, organizational structure, value systems, information flow, and conflict resolution within SMOs. The methodology involved theoretical sampling, prioritizing expert self-management knowledge over mere representativeness. Seven nurses, twelve management members, and fifteen patients from self-managed homecare organizations contributed to the examination of nursing experiences. Constant comparative analysis of data led to the identification of the Qualitative Success Enablers (QSEs), revealing three themes: Insightfulness, Enhancing Nursing Experience through Job Enrichment, and Autonomy-Enabled Intrapreneurship. Results: The findings indicate that the horizontal management structure represented by the studied organization in India has shown considerable success in times laden with uncertainties during the COVID-19 pandemic, especially during the delta wave, which revealed the frailty of existing healthcare infrastructure. The organization successfully maintained a better nursing experience and gained patient and employee satisfaction, as revealed by in-depth semi-structured interviews and constant comparative analysis. Conclusion: In a world of unique challenges, we stand on the brink of significant transformations. SMOs are vital in India’s homecare sector for enhancing nursing experiences and overall organizational performance. Fostering a trust-based environment within SMOs is integral to delivering effective services. The autonomy to design nursing jobs, insightfulness, and innovativeness in the nursing job through suitable training activities, various job enrichment methods, and finding meaningfulness in a job through softer aspects of caregiving result in an enhanced nursing experience at SMOs. This groundbreaking approach can be extended to other homecare organizations in India, relieving the strain on the existing healthcare system. © 2023, The Author(s).